Antiproliferative and proapoptotic effects of DODAC/synthetic phosphoethanolamine on hepatocellular carcinoma cells - Arthur Cássio de Lima Luna; Greice Kelle Viegas Saraiva; Gilberto Orivaldo Chierice; Henrique Hesse; Durvanei Augusto Maria (BMC, 2018)
Abstract Background Current studies have demonstrated that DODAC/PHO-S (Dioctadecyldimethylammonium Chloride/Synthetic phosphoethanolamine) liposomes induces cytotoxicity in Hepa1c1c7 and B16F10 murine tumor cells, with a higher proportion than PHO-S. Therefore, our aim was to evaluate the potential of DODAC/PHO-S to elucidate the mechanism of cell death whereby the liposomes induces cytotoxicity in hepatocellular carcinoma Hepa1c1c7, compared to the PHO-S alone. Methods Liposomes (DODAC/PHO-S) were prepared by ultrasonication. The cell cycle phases, protein expression and types of cell's death on Hepa1c1c7 were analyzed by flow cytometry. The internalisation of liposomes, mitochondrial electrical potential and lysosomal stability were also evaluated by confocal laser scanning microscopy. Results After treatment with liposomes (DODAC/PHO-S), we observed a significant increase in the population of Hepa1c1c7 cells experiencing cell cycle arrest in the S and G2/M phases, and this treatment was significantly more effective to promote cell death by apoptosis. There also was a decrease in the mitochondrial electrical potential; changes in the lysosomes; nuclear fragmentation and catastrophic changes in Hepa1c1c7 cells. The liposomes additionally promoted increases in the expression of DR4 receptor, caspases 3 and 8, cytochrome c, p53, p21, p27 and Bax. There was also a decrease in the expression of Bcl-2, cyclin D1, CD90 and CD44 proteins. Conclusion The overall results showed that DODAC/PHO-S liposomes were more effective than PHO-S alone, in promoting cytotoxicity Hepa1c1c7 tumor cells, activating the intrinsic and extrinsic pathways of programmed cell death.